Comparative efficacy of organic and inorganic amendments for cadmium and lead immobilization in contaminated soil under rice-wheat cropping system. (January 2019) - Hamid, Yasir; Tang, Lin; Yaseen, Muhammad; Hussain, Bilal; Zehra, Afsheen; Aziz, Muhammad Zahir; He, Zhen-li; Yang, Xiaoe
Abstract: Field experiments were conducted in two consecutive rice-wheat cropping seasons on a yellow clay soil to assess the efficacy of organic and inorganic amendments for cadmium (Cd) and lead (Pb) immobilization. Amendments were applied alone and in combinations to compare their efficacy for metals immobilization. Composite amendment of GSA-4 (Green Stabilizing Agent) and biochar resulted in higher biomass and grains yield for both rice ( Oryza sativa L.) and wheat ( Triticum aestivum L.). Liming, DEK1 (Di Kang No. 1) or GSA-4 amendment increased soil pH from 6.34 to 7.35, 7.20 and 7.15, respectively. Soil amendments significantly reduced DTPA extractable Cd and Pb in soil at wheat harvest. Cadmium and Pb fractionation showed a significant decrease in the extractable fractions by the amendment of biochar (34% and 25%) or GSA-4 (35% and 26%, respectively). GSA-4 and biochar amendment enhanced metals immobilization and reduced their uptake by plant and subsequent accumulation in the grains of rice and wheat, particularly with GSA-4. These results indicate that GSA-4 and biochar, especially their combination, have great potential for application to remediate Cd and Pb contaminated soils. Graphical abstract: Image 1 Highlights: This manuscript shares findings about Cd and Pb immobilization with soil amendments. Soil pH changes directly influenced heavy metals stabilization in soil. Composite amendments reduced trace metals accumulation in rice and wheat grains. Amendments effect on physiological changes in plants need to be addressed in future.